2020
DOI: 10.3389/fpsyg.2020.00268
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Posterior and Anterior Insula Activations in Processing Negative Stimulus Before and After the Application of Cognitive Reappraisals

Abstract: Although the role of the insular cortex in representing bodily and emotional feelings has been recognized, whether the mid-posterior and anterior parts of the insula act differentially in the encoding and regulation of emotional feelings is still unclear. In this functional magnetic resonance imaging (fMRI) study, we examined the effects of the creative cognitive reappraisals versus the non-creative ordinary reappraisals on the activation pattern of the mid-posterior and anterior insular cortex during the proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Our results of reinterpretation reducing posterior and increasing anterior insula activation are in correspondence with previous findings showing the same activation pattern for affective stimuli from pre to post cognitive reappraisal by reinterpretation ( Zhang et al , 2020 ). These findings are also interpreted with regard to Craig’s posterior to anterior distinction of the insula ( Craig, 2009 ). While posterior insula activation might reflect reduced experience of negative feelings, increased anterior insula activation might more likely be associated with enhanced cognitive processing after reinterpretation.…”
Section: Discussionsupporting
confidence: 93%
“…Our results of reinterpretation reducing posterior and increasing anterior insula activation are in correspondence with previous findings showing the same activation pattern for affective stimuli from pre to post cognitive reappraisal by reinterpretation ( Zhang et al , 2020 ). These findings are also interpreted with regard to Craig’s posterior to anterior distinction of the insula ( Craig, 2009 ). While posterior insula activation might reflect reduced experience of negative feelings, increased anterior insula activation might more likely be associated with enhanced cognitive processing after reinterpretation.…”
Section: Discussionsupporting
confidence: 93%
“…The insula, receiving and sending out information to limbic-related structures, plays an important role in emotional processing, particularly negative emotion processing ( Shah et al. , 2009 ; Zhang et al. , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The major experimental materials were 40 unpleasant pictures from the IAPS (Lang et al, 2005) together with corresponding cognitive reappraisal sentences of high and low creativity, taken from the cognitive reappraisal item pool that was established for the unpleasant IAPS pictures (X. Wu et al, 2017Wu et al, , 2019Zhang et al, 2020). The images included a variety of unpleasant stimuli and situations, such as threat/attack scenes, animals, and disgusting stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the application of creative reappraisals could be associated with brain action in the key regions or networks mediating the process of cognitive restructuring and emotion improvement (X. Wu et al, 2019), implying that the function of this regulation is creating insight or cognitive restructuring (see Shen et al, 2017 for a review) and increasing positive emotion. Creative reappraisals were also found to be more capable of transferring emotional feelings represented in the posterior insular cortex to the anterior part of the insular cortex, implying a more intensive cognitive modulation of internal emotional feelings (Zhang et al, 2020). In addition, our recent study found that the creative humor coping with unpleasant emotions accompanied by viewing negative pictures could be realized through the “aha!…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation